F. Michael Higginbotham, Ghosts of Jim Crow: Ending Racism in Post-Racial America - Anna Scacchi (Iperstoria, 2014)
Review of Ghosts of Jim Crow: Ending Racism in Post-Racial America by F. Michael Higginbotham